Optimizing Investments in Kazakhstan's HIV Response - World Bank (World Bank, Washington, DC, 2016)
As part of a Regional initiative, Kazakhstan conducted an Human Immunodeficiency Virus (HIV) allocative efficiency analysis in 2014 to 2015 to inform more strategic investment in HIV programs. Kazakhstan continues to experience a concentrated HIV epidemic in which the majority of new infections occurred among key populations, particularly PWID, MSM, prison inmates, FSW, and their clients. Under current conditions (constant behaviors and program coverage), new HIV infections are projected to rise by 13 percent and deaths by 32 percent. The epidemics among PWID and MSM are projected to account for 67 percent of new HIV infections from 2015 to 2020 so need to be a core focus of programs. With optimized allocations, the cost to achieve national targets (no increase in incidence and deaths from 2015 to 2020) would be US 52 million dollars per year. The cost to achieve more ambitious future HIV response targets was estimated at US 80 million dollars.In conclusion, a combination of various efficiency gains in Kazakhstan’s HIV response can halve new HIV infections and deaths, achieving ambitious national targets at no additional cost. As a first priority, ART will be essential for reducing deaths and new infections, but unit costs need to be reviewed and reduced. A second consistent finding is the continued need to provide HIV services for PWID at scale. A third consistent finding is the need to scale up programs for MSM and at least double the current low coverage levels. Additional technical efficiency analysis is worth considering to explore the concrete pathways to achieve the proposed cost reductions for ART, OST, and management costs.